The perilous state of seagrass in the British Isles. Issue 1 (January 2016) - Jones, Benjamin L.; Unsworth, Richard K. F.
Abstract : Seagrass ecosystems face widespread threat from reduced water quality, coastal development and poor land use. In recent decades, their distribution has declined rapidly, and in the British Isles, this loss is thought to have been extensive. Given increasing knowledge of how these ecosystems support fisheries production, the understanding of their potential rapid loss, and the difficulty in restoring them, it is vital we develop an understanding of the risks they are under, so that management actions can be developed accordingly. Developing an understanding of their environmental status and condition is therefore critical to their long-term management. This study provided, to our knowledge, the first examination of the environmental health of seagrass meadows around the British Isles. This study used a bioindicator approach and involved collecting data on seagrass density and morphology alongside analysis of leaf biochemistry. Our study provides, to the best of our knowledge, the first strong quantitative evidence that seagrass meadows of the British Isles are mostly in poor condition in comparison with global averages, with tissue nitrogen levels 75% higher than global values. Such poor status places their long-term resilience in doubt. Elemental nutrient concentrations and morphological change suggest conditions of excess nitrogen and probable low light, placing many of the meadows sampled in a perilous state, although others, situated away from human populations were perceived to be healthy. Although some sites were of a high environmental health, all sites were considered at risk from anthropogenic impacts, particularly poor water quality and boating-based disturbances. The findings of this study provide a warning of the need to take action, with respect to water quality and disturbance, to prevent the further loss and degradation of these systems across the British Isles.